SOSIOLOGI PENDIDIKAN ISLAM: ANALISIS KONSEP, TUJUAN, DAN DINAMIKA HUBUNGAN MASYARAKAT DAN PENDIDIKAN - Achmad Junaedi Sitika; Nuur'Atikah Mufidah; Rafik Ramdani; Nazwa Nur Aulia Syam; Muhammad Aly Fadhillah; Fawwas Hafish Harsoyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to analyze the sociological concept of Islamic education, the goals of Islamic education, and the dynamics of the relationship between society and education. The research uses a qualitative approach with library research methods through reviewing various relevant books, journals and scientific articles. The research results show that the sociology of Islamic education is a study that studies the reciprocal relationship between education, Islamic values ​​and the social life of society. Islamic education functions not only as a process of transferring knowledge, but also as a means of forming students' character, morals and social NBBJMBJBJBBNattitudes. In addition, the relationship between society and education is dynamic because it is influenced by social, cultural, economic and technological developments. Changes in society can influence the Islamic education system, both in learning methods and educational goals. On the other hand, Islamic education also has an important role in forming a society that is religious, harmonious and has noble morals. Thus, the sociology of Islamic education becomes an important basis in understanding the role of education as an agent of social change oriented towards Islamic values ​​and the needs of modern society.